Homossexualidade e Direitos Humanos (I, II) - Soares da Costa, Wellington (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article is not a vast and exhaustive analysis of all the interfaces in which homosexualism has been shrouded. Nevertheless, what is intended is to urge the reader to undertake a precise study in a juridical context of a theme which is so relevant.
Keywords: homosexualism; Human Rights; human dignit; citizenship